Dysregulation of intestinal epithelial electrolyte transport in canine chronic inflammatory enteropathy and the role of the renin-angiotensin-aldosterone-system - Dengler, Franziska; Domenig, Oliver; Kather, Stefanie; Burgener, Iwan A.; Steiner, Joerg M.; Heilmann, Romy M. (Frontiers in Veterinary Science, 2023)
Chronic diarrhea is a hallmark sign of canine chronic inflammatory enteropathy (CIE), leading to fluid and electrolyte losses. Electrolyte homeostasis is regulated by the renin-angiotensin-aldosteronesystem (RAAS), which might be involved in (counter-)regulating electrolyte losses in canine CIE. Whether and which electrolyte transporters are affected or if RAAS is activated in canine CIE is unknown. Thus, intestinal electrolyte transporters and components of the RAAS were investigated in dogs with CIE. Serum RAAS fingerprint analysis by mass spectrometry was performed in 5 CIE dogs and 5 healthy controls, and mRNA levels of intestinal electrolyte transporters and local RAAS pathway components were quantified by RT-qPCR in tissue biopsies from the ileum (7 CIE, 10 controls) and colon (6 CIE, 12 controls). Concentrations of RAAS components and mRNA expression of electrolyte transporters were compared between both groups of dogs and were tested for associations among each other. In dogs with CIE, associations with clinical variables were also tested. Components of traditional and alternative RAAS pathways were higher in dogs with CIE than in healthy controls, with statistical significance for Ang I, Ang II, and Ang 1-7 (all P<0.05). Expression of ileal, but not colonic electrolyte transporters, such as Na+/K+-ATPase, Na+/H+-exchanger 3, Cl-channel 2, down-regulated in adenoma, and Na+-glucose-cotransporter (all P<0.05) was increased in CIE. Our results suggest that the dys-or counter-regulation of intestinal electrolyte transporters in canine CIE might be associated with a local influence of RAAS. Activating colonic absorptive reserve capacities may be a promising therapeutic target in canine CIE.